2022
DOI: 10.21203/rs.3.rs-1808133/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Severity of Omicron (B.1.1.529) and Delta (B.1.1.617.2) SARS-CoV-2 infection among hospitalised adults: a prospective cohort study

Abstract: Limited data exist assessing severity of disease in adults hospitalised with Omicron SARS-CoV-2 variant infections, and to what extent patient-factors, including vaccination and pre-existing disease, affect variant-dependent disease severity. This prospective cohort study of all adults (≥18 years of age) hospitalised at acute care hospitals in Bristol, UK assessed disease severity using 3 different measures: FiO2 >28%, World Health Organization (WHO) outcome score >5, and hospital length of stay (LOS) &g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 19 publications
5
15
1
1
Order By: Relevance
“…In contrast, the cumulative mortality of Omicron was 0.31–0.41 times the death of Delta variant. These results accord with cohort studies which found Omicron infection has a lower risk of severe outcomes than Delta ( Hyams et al, 2022 ; Nyberg et al, 2022 ). For instance, in the contact setting without stringent lockdowns, we estimated that in a potential Omicron wave, only 4.7% of infections would occur in Fujian Province among individuals aged >60 years, while 58.75% of the death toll would occur in unvaccinated individuals aged >60 years (14,271 people).…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, the cumulative mortality of Omicron was 0.31–0.41 times the death of Delta variant. These results accord with cohort studies which found Omicron infection has a lower risk of severe outcomes than Delta ( Hyams et al, 2022 ; Nyberg et al, 2022 ). For instance, in the contact setting without stringent lockdowns, we estimated that in a potential Omicron wave, only 4.7% of infections would occur in Fujian Province among individuals aged >60 years, while 58.75% of the death toll would occur in unvaccinated individuals aged >60 years (14,271 people).…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the vaccination status, consistent with previous data from both general population and hospitalized patients, [19][20][21][22][23][24][25][26][27][28][29] we found a higher probability of prior full vaccination among Omicron infected individuals, likely due to the mechanism of immune evasion described for this viral variant. [12][13][14] Although this aspect has led to questions about whether the lower severity of Omicron infections may be due to an inherent characteristic of the variant or to the wide vaccination coverage, several studies have confirmed the lower severity of Omicron compared with Delta infections also in the unvaccinated population.…”
Section: Nasopharyngeal Viral Loads Comparisonsupporting
confidence: 90%
“…In particular, patients infected with Omicron VOC had a median age 7 years higher than those with Delta and more than half of them reported at least two underlying comorbidities at hospital admission as compared to less than 40% of patients infected with Delta. This data is in contrast with previous studies conducted in both outpatient 21–23 and inpatient 25–27 healthcare settings, which described a younger median age and a similar or lower comorbidity burden of patients with Omicron compared to Delta infection but are in line with recent observations from Belgian 28 and British 29 cohorts of hospitalized patients. These discrepancies among available studies can be explained by several reasons, such as different approaches and timing of the vaccination campaign, public health measures, and testing strategies.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…33 The number of deaths averted per administered dose was significantly higher in high-income countries, which has also been attributed to higher access and uptake of the more efficacious mRNA vaccines. 33 Moreover, studies show that scaling up mRNA vaccinations against COVID-19 in lower-to-middleincome countries during the dominance of the clinically less significant Omicron severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variant [34][35][36] would bring substantial benefits in terms of averted deaths and could be an economically reasonable approach. 37 At the same time, mRNA vaccines are well-accepted by individuals who do not reveal significant vaccine hesitancy.…”
Section: Introductionmentioning
confidence: 99%